The Frequency of Frailty in Ambulatory Patients With Chronic Lung Diseases - Neha Mittal; Rishi Raj; Ebtesam Attaya Islam; Kenneth Nugent (SAGE Publishing, 2016)
Objectives: To determine the prevalence of frailty in patients with chronic lung diseases. Methods: We studied 120 patients with chronic lung disease using Fried's criteria (gait speed, weight loss, exhaustion, grip strength, and physical activity). Results: The study population (56% women) had a mean age of 64 ± 13 years, mean body mass index of 31± 9 kg/m 2 , and a mean FEV 1 (forced expiratory volume in 1 second) of 60% ± 25% of predicted. The average gait speed was 52.1 ± 14.3 m/min; 18% were frail, 64% prefrail, and 18% robust. Gait speed correlated with frailty status and decreased as frailty worsened (57 m/min in robust subjects and 41 m/min in frail subjects). Slow gait speeds (<60 m/min) had a 95% sensitivity and 34% specificity to predict frailty. Conclusions: Patients with chronic lung disease frequently meet Fried's criteria for frailty. Gait speed can be used to screen these patients to determine if a more detailed evaluation is needed.